Immediate Effect of Vestibular Exercise on Blood Pressure in Healthy Females - Dr SaiSailesh Kumar G (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Both animal and human studies reported that stimulation of vestibular system alleviates stress and regulates blood pressure. Vestibular stimulation was reported to modulate the blood pressure and respiration through brainstem inhibitory mechanisms. Objective The present study was undertaken to observe the immediate effect of vestibular exercises on blood pressure in healthy females. Methodology A total of thirty apparently healthy female participants were included in the study after obtaining the written informed consent. Those with serious complications, following any treatment or therapy and unwilling participants were excluded from the study. Blood pressure and heart rate was recorded using JSB fully automatic upper arm style Blood Pressure Monitor (Model: DBP05 digital arm BP monitor).After recording the baseline blood pressure, the participants were asked to performsix minutes of vestibular exercises according to the Cawthrone and Cooksey’s protocol which includes, walking in a straight line while looking sideways, throwing ball from one hand to the other by fixing gaze on the ball, walking straight and throwing ball from hand to hand by fixing gaze on the ball. Duration ofeach exercise was fixed for two minutes by trial and error method. Immediately after the exercise, blood pressure was recorded and compared. Results There was a decrease in systolic blood pressure followed by vestibular exercise. However, it was not statistically significant. There was a significant decrease (P<0.05) in diastolic blood pressure followed by vestibular exercise. Conclusions Significant decrease in the diastolic pressure but not systolic blood pressure was observed followed byvestibular exercise. We recommend further detailed studies in this area to understand the effect of vestibular exercises on blood pressure, which helps to recommend adoption of vestibular exercises in the management of hypertension.